Successful management of belimumab after obinutuzumab in a patient with systemic lupus erythematosus: a case report with an 18-month follow-up - Pu, Xiuxiu; Ye, Qiao; Zhu, Lin; Yan, Tingting (Frontiers in Immunology, 2024)
Introduction Systemic lupus erythematosus (SLE) is a complex autoimmune disease, and despite the availability of multiple treatments, striking a balance between long-term efficacy and side effects remains a major clinical challenge. B-cell–directed therapy has attracted much attention because of its unique mechanism of action. Belimumab and obinutuzumab, as representative drugs for B-cell–directed therapy, have shown their respective advantages for SLE treatment. However, data on combination therapy with obinutuzumab and belimumab are currently unavailable. Case presentation We present the severe case report of a patient who was diagnosed with lupus nephritis (LN) with gastrointestinal involvement and developed acute renal failure. The patient responded to the first dose of obinutuzumab but failed to achieve a complete response to LN. The repeated use of obinutuzumab was limited by persistently low IgG levels and frequent infections. This is a real-world challenge that must be addressed. Therefore, the patient was subsequently treated with a novel sequential regimen of obinutuzumab followed by belimumab. After 18 months of follow-up, the patient achieved a complete clinical response with a favourable safety profile, along with the conversion of all autoantibodies from positive to negative and sustained negativity. To date, the patient has achieved a dual clinical and serological response. Conclusion There is a reason to believe that this novel combination regimen could be developed as a therapeutic strategy, with the expectation of balancing efficacy and safety.